Analysis of the effect of smaw welding current variation on the quality of AISI 1041 steel material joints - Saifuddin, Saifuddin; Syahandra, Muhammad Arga; Azwinur, Azwinur (Journal of Mechafa Engineering and Fabrication, 2025)
This study analyzes the effect of E7018 electrode current variation on SMAW welding process on AISI 1041 steel material, using penetrant test and bending test as evaluation methods. AISI 1041 steel is often used in construction industry because of its good mechanical properties and its ability to be welded with various techniques. Testing was conducted with welding current variation of 100 A, 110 A, and 120 A. The test results showed that welding current significantly affected the strength and resistance of the material to deformation. At 110 A current, the material showed an optimal combination of strength and flexibility. Higher current (120 A) tended to increase the maximum stress in Root Pass test, but decreased the strength in Capping. This finding emphasizes the importance of selecting the right welding current in determining the strength of the welded joint, in addition to considering heat distribution and changes in material microstructure.